Health-Based Physical Education Learning Model: A Literature Review of Global Practices - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This systematic literature review explores global practices in implementing Health-Based Physical Education (HBPE) models, aiming to identify key strategies, outcomes, and contextual factors influencing success. Using databases such as Scopus, PubMed, ERIC, ScienceDirect, and SINTA, 62 peer-reviewed articles published between 2014 and 2024 were analyzed through thematic synthesis. The review categorizes HBPE models into thematic health-oriented learning, structured physical activity programs (e.g., TPSR, SEPEP), and technology-assisted models (e.g., wearable fitness devices, digital PE platforms). Findings show that HBPE significantly contributes to improving students’ physical health and behavioral outcomes. For example, a controlled study in Canada demonstrated a 23% improvement in cardiorespiratory fitness after a 12-week HBPE intervention (Thomas et al., 2021). In South Korea, schools implementing HBPE integrated with mindfulness training reported reduced stress levels and improved classroom behavior (Lee & Kim, 2020). Across regions, success factors included teacher professional development, supportive national policies, availability of facilities, and cultural alignment of curricula. However, challenges persist, such as inconsistent funding, limited teacher expertise, and socio-cultural barriers in low- and middle-income countries. The review concludes that HBPE is a globally viable model for promoting lifelong health in students, particularly when contextualized to local educational frameworks. Recommendations include investing in teacher training, curriculum innovation, and multi-sector collaboration. This review provides policymakers, educators, and researchers with a comprehensive understanding of global HBPE practices and their relevance to improving the quality and inclusivity of physical education